2021
DOI: 10.1177/03000605211013176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of focused cardiopulmonary ultrasonography on clinical outcome of septic shock: a randomized study

Abstract: Objective To investigate the effect of focused ultrasonography on clinical outcomes of septic shock. Methods Patients with septic shock were randomized into an integrated cardiopulmonary ultrasonography (ICUS) group and conventional (CON) group. Within 1 hour of admission, the ICUS group underwent ICUS examination for hemodynamic decision-making, while the CON group received standard treatment. The primary endpoint was 28-day mortality after admission. The secondary endpoints were cumulative fluid administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The adult RCT from China, much like our study, assessed lung ultrasound, ejection fraction, IVC variations, and additionally RV dilatation but only at a single time point. 22 Cumulative fluid balance at 72 hours, vasoactive drug usage, lactate clearance, duration of ventilation, and ICU stay were similar in both groups. The author stated that lesser number of patients (22.4%) than expected had abnormal ultrasound findings, which weakened its clinical effect.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The adult RCT from China, much like our study, assessed lung ultrasound, ejection fraction, IVC variations, and additionally RV dilatation but only at a single time point. 22 Cumulative fluid balance at 72 hours, vasoactive drug usage, lactate clearance, duration of ventilation, and ICU stay were similar in both groups. The author stated that lesser number of patients (22.4%) than expected had abnormal ultrasound findings, which weakened its clinical effect.…”
Section: Discussionmentioning
confidence: 80%
“…Comparable to our observation, lengths of ICU and hospital stay were similar in both groups of the adult studies. 20 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult and pediatric intensive care units, integrated CPUS has shown a significantly better performance than LUS alone in the diagnosis of acute respiratory failure, being particularly useful to distinguish cases of hemodynamic pulmonary edema and pneumonia, often changing the clinical approach and management [ 87 ]. The CPUS approach leads to a shorter duration of vasopressor support [ 88 ]. Recently, it has been shown that in neonates, the expertise in CPUS interpretation to guide neonatal shock can be achieved in a relatively short time [ 89 ].…”
Section: Cardiopulmonary Ultrasoundmentioning
confidence: 99%
“…Scanning physicians were POCUS experts, not involved in patient management but not blinded to obvious clinical signs. Li et al [89] conducted an outcome study in 94 patients of whom 49 received POCUS and found no difference in 28-day mortality. The clinical effect might have been subtle because of a small number of patients with abnormal ultrasound findings.…”
Section: The Impact Of Pocus In Patients With Nontraumatic Hypotensio...mentioning
confidence: 99%